Two commentaries. Confessions of a Boomer (inOpera Esercizi di lettura su testi contemporanei, 2024)
In a retrospective way, two commentaries on twentieth-century Italian poets, Vittorio Sereni and Guido Gozzano, published respectively in 1990 and 1995, are the subject of reflection. By highlighting the specific critical approach to individual authors, the commentator's work is framed in a conception at the same time empirical and non-conformist, attentive to the structural constants and to the key words of the works examined.
Keywords: Vittorio Sereni; Guido Gozzano; Prose and poetry; Intertextuality; Cesare Garboli